Effects of heat transfer coefficient variations on composite curing. (February 2023) - Fisher, Adam; Levy, Arthur; Kratz, James
Curing of composite laminates in a vessel was investigated in this study. The environment inside the processing vessel dictates the efficiency and ultimately drives the quality of thermoset composite parts. Experimental measurements of spatial heat transfer coefficients were conducted on industrial scale vessels, including autoclaves and large ovens, which ultimately drives the quality of thermoset composite parts. The final part quality was investigated using the experimental data as input to a coupled heat transfer and curing model. Measurements showed that heat transfer coefficients in autoclaves were greater in magnitude and spatial variability. The distribution in the autoclaves followed a pattern common in the literature, in contrast to that in the ovens which varied considerably between devices. Numerical predictions indicated autoclave measured heat transfer coefficients provide less lag to the imposed temperature history and smaller temperature overshoots. However, the greater robustness to variability at autoclave heat transfer coefficients was offset by the greater variability, resulting in comparable robustness across the ovens and autoclaves.